Ammonia and Liquid Hydrogen as Energy Carriers: Challenges and Opportunities - Gihong Lee; Seungyun Lee; Saerom Hong; Hokyoung Jung; Sokhee P. Jung (대한환경공학회지)
The artificial synthesis of ammonia has significantly contributed to addressing global hunger by enhancing agricultural productivity. This achievement led to an explosive increase in population, with the current global population surpassing 8 billion. However, this rapid population growth has also accelerated environmental pollution and the climate change crisis. Recently, the use of ammonia as an energy carrier has garnered attention as part of efforts to combat climate change. Due to the challenges associated with storing and transporting hydrogen, converting it into ammonia for use as an energy carrier is being actively studied. Ammonia is more stable and cost-effective for storage and transportation than hydrogen because of its higher boiling point (-33.34°C vs. -252.9°C) and larger molecular weight (17 vs. 2). However, additional infrastructure is required for the conversion between hydrogen and ammonia, and this process results in energy losses. In this review, the costs and energy efficiencies of using ammonia and liquefied hydrogen as energy carriers were analyzed based on 1 ton of hydrogen production and consumption: 1) In terms of cost, ammonia was estimated at 6,548,200 KRW, while liquefied hydrogen was 7,900,000 KRW. 2) The energy efficiency of fuel cell vehicles was 18.5% for ammonia and 23% for liquefied hydrogen. 3) For residential fuel cells, the energy efficiency was 33% for ammonia and 41% for liquefied hydrogen. Although ammonia exhibits lower energy efficiency compared to liquefied hydrogen as an energy carrier, it is relatively competitive in terms of economic viability. However, the conversion between hydrogen and ammonia requires additional facilities, and significant energy losses occur during this process. These limitations have led to growing interest in the direct combustion of ammonia. In addition, technologies for directly using renewable electricity or storing it in batteries without energy carriers are being continuously developed. As such, the future of energy technology will gradually take shape through intense competition among various innovative solutions.